Analisa Kerusakan Bantalan SKF 6305 Pada Carrier Idler Di PT.SEMEN INDONESIA (PERSERO) - Doni Fauzi Muhamad; So’im Subagio; Sudiyono Sudiyono (Proceedings Conference on Marine Engineering and its Application, 2018)
Conveyor belt at PT. SEMEN INDONESIA is a coal transporter from ship to land. On the conveyorsection there is a slacker that functions as a belt buffer. In idling, some can work to support the idler shaft so that theidler shaft can rotate without excessive pressure. The pads on the idler often fail, especially bearing on the bottom ofthe chute transfer. Besides that, coal transportation factor is also one of the factors causing the failure of bearings.Coal transported by belt conveyors at PT. SEMENT INDONESIA there are two types of bituminous and anthracitecoal. Types of bearing damage that occur in PT. SEMENT INDONESIA is crack, pear skin, discoloratioan, wear,smearing, and corrosion. From the data and calculation results obtained, it is necessary to periodically check thatthe treatment can be carried out properly so that the equipment has a long service life. To find out the causes of whyit can happen, more research is carried out on bearings to get accurate data about the failures that occur on thebearing.